Webcam-Based Bus Passenger Detection System Using Single Shot Detector Method - Wasista, Sigit (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
Buses are one of the most widely chosen transportation methods to support the mobility of the Indonesian people. Mobility that is often found in addition to public transportation, is also often found in the mobility of tourism tour activities for a travel group. The number of tourist destinations to which passengers go up and down makes the assistant bus driver or group leader work hard to ensure that the number of passengers boarding the bus matches the number of groups. It often takes a long time to ensure the accuracy of the number of passengers before departure to the next destination. This conventional method results in the delay of the tourism tour schedule. In this research, the author designs a webcam-based bus passenger face detection system using the Single Shot Detector (SSD) method that can provide real-time information to bus drivers, assistant bus drivers or group leaders. The results obtained by the system obtained an achievement of 95% of the total system creation along with testing the detection of bus passenger faces in actual conditions resulted in an average accuracy of 77.5%.